Time to recovery from Eclampsia and its determinants in east Gojjam zone hospitals, Amhara, Ethiopia, 2017/18 - Bekalu Kassie; Yibelu Bazezew; Yewbmirt Sharew; Leltework Yismaw; Melaku Desta; Muluneh Alene (BMC, 2021)
Abstract Background Eclampsia is a tonic clonic type of seizure among pre-eclamptic mothers. Time to recovery from eclampsia is to mean that the time when the mother recovered from severity features of pre-eclampsia. As far as the mother is not free from severity features, she is in a potential to end-up with repeated seizure (eclampsia). Therefore, combating eclampsia through controlling severity features is crucial to enhance maternal health quality, reduce maternal morbidity and mortality, and improve prenatal outcomes. There was no literature that describes the recovery time of eclampsia and its determinants in Ethiopia. Therefore, this study aimed to assess the recovery time from eclampsia and its determinants in East Gojjam zone hospitals. Methods An institutional based retrospective follow up study was conducted between January 2014 and December 2017 among 608 eclamptic mothers in East Gojjam zone Hospitals. Simple random sampling technique was used. Data were coded and entered to Epidata version 3.1 and was exported to SPSS version 20 and then to Stata 14. We used the adjusted hazard ratio (AHR) with 95% confidence interval at p-value less than 0.05 to measure strength of association. Result The median recovery time of eclampsia was 12 h with inter-quartile range of (1-48 h). The rate of recovery from eclampsia among mothers aged more than 20 years was reduced by half (AHR 0.50 (0.28, 0.89)) than the teenagers. The rate of recovery from eclampsia among mothers who had prolonged labor was 1.3 times (AHR 1.26 (1.01, 1.57)) than those whose labor was less than 12 h. About 32% of mothers with multiple convulsions recoverd later than (AHR 0.68 (0.52, 0.87)) those who had single convulsion. As compared to antepartum convulsion, the rate of recovery from postpartum eclampsia was 1.8 times faster (AHR 1.81(1.17, 2.81)). Conclusion The median recovery time from severity features among eclamptic mothers in East Gojjam zone hospitals was half a day. It is affected by age, duration of labor, number of convulsions and time of occurrence of the event. Special attention for elders, prevent recurrent convulsion and faster termination for the antepartum eclamptic mothers are recommended from this follow-up study.